126k views
0 votes
F(x)=x

3
−6f, left parenthesis, x, right parenthesis, equals, x, start superscript, 3, end superscript, minus, 6
h(x)=\sqrt[\Large3]{2x-15}h(x)=
3

2x−15
​ h, left parenthesis, x, right parenthesis, equals, root, start index, 3, end index, square root of, 2, x, minus, 15, end square root
Write f(h(x))f(h(x))f, left parenthesis, h, left parenthesis, x, right parenthesis, right parenthesis as an expression in terms of xxx.
f(h(x))=f(h(x))=f, left parenthesis, h, left parenthesis, x, right parenthesis, right parenthesis, equals

User Officer
by
4.8k points

1 Answer

4 votes

2x - 21

......................

User Hurrtz
by
4.8k points